Performance Evaluation of Bedding Sand and Load Transfer Characteristic of Concrete Block Pavements - Wuguang Lin (MDPI AG, 2021)
Concrete block pavement is used as a modern pavement type owing to its economic benefits. The physical properties, mechanical properties, and functional characteristics of bedding sand and joint sand, the main components of concrete block pavements, should be accurately understood. Owing to the discontinuous structure of these pavements, load transfer efficiency (LTE) is the most important index from the perspective of performance. The factors that affect LTE are bedding sand (type, grading, and thickness), joint sand (type and grading), and concrete block (shape and pattern). Therefore, the optimal design for concrete block pavements can be achieved by analyzing each factor. In this study, three types of sand (river, quartz, and manufactured) were selected to examine the mechanical properties via direct transfer experiments. It was observed that the shear strength of river sand was the highest. It was also found that the difference between the shear strength and the internal friction angle (according to the content of 0.6 mm in the grading of bedding sand) was not large, and the shear strength and the friction angle increased as the content increased to 0.075 mm. In addition, the load transfer characteristics of the joint and rotational interlocking of the block were evaluated through a non-destructive test using the degree of joint filling, block shape, and construction pattern as variables. As a result, the degree of joint filling had the greatest effect on the load transfer characteristics of the joint and rotational interlocking of the block. The effect of the block shape was larger than that of the construction pattern. When a heavy load is applied, the LTE between blocks must be maintained at 50% or more, and the rotation of blocks at 0.6° or less, if 75% or more of the joint must be filled for preventing excessive vertical deformation.